Hubungan Kualitas Produk dan Harga terhadap Pembelian Ulang Pia Baturiti Cap Sinar - DEWI, NI PUTU FEBRI KRISNA; SUSRUSA, KETUT BUDI; IGAA LIES ANGGRENI, IGAA LIES ANGGRENI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2021)
The Relationship Between Product Quality and Price on The Repurchase  of Pia Sinar Baturiti Nowadays, people tend to prioritize taste and nutrition, only then consider the price when buying food. Bread is a choice of snacks considering the variety of flavors offered and contains good nutrition. In terms of price, bread is easily accessible to all people. This study aims to determine the relationship between product quality and Pia Sinar Baturiti repurchase, as well as the relationship between price and Pia Sinar Baturiti repurchase. Primary data is obtained through a questionnaire given to consumers who have repeatedly bought Pia Sinar Baturiti. The analysis used is a quantitative analysis, namely Rank Spearman analysis. Based on the research, the characteristics of consumers who repurchase Pia Sinar Baturiti are women (54.1%), high school graduates (45.9%), private employees (28.2%) and traders (25.9%). The dominant variable that has a repurchase relationship is the variable of product quality with a correlation value of 0.612 with a strong correlation level, and the variable of price with a correlation value of 0.568 with a moderate level of relationship.